Peluang dan Tantangan Penggunaan Tiktok sebagai Sarana Komunikasi bagi Masyarakat Baduy Luar di Provinsi Banten - Juliansyah, Adi Akhyardi; Samad, M. Yusuf; Permatasari, Diah Ayu; Persadha, Pratama Dahlian (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2025)
The increased political participation of the Outer Baduy community in the 2019 General Election shows the influence of access to digital information, including social media. TikTok social media has become an interactive political communication platform, allowing the Outer Baduy community to access and disseminate political messages. However, the use of TikTok social media in the political communication of the Outer Baduy community presents both opportunities and challenges in the process of socialization and delivery of political information. This research aims to explore the use of TikTok social media as an alternative political communication for the Outer Baduy community. The approach used is a descriptive qualitative approach with a literature study. The results show that TikTok offers significant opportunities in political communication, for political actors and indigenous people due to its ability to reach a wide audience and provide more personalized interactions. However, there are challenges such as optimizing the use of TikTok by political actors and implementing digital literacy that is sensitive to local culture, especially in communities such as Baduy. Thoughtful and context-based use of TikTok can strengthen political participation and social inclusivity, it needs to be accompanied by efforts to address disinformation and maintain existing cultural values.